Językowe sposoby kształtowania obrazu "prawdziwego mężczyzny" (na podstawie analizy wyników badań korpusowych) = Linguistic ways shaping the image of "a real man" (based on the analysis of the results of corpus studies) - Ścigała-Stiller, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of this article is to present linguistic ways of shaping the image of a real man. These studies describe the lexical connectivity of the expression a real man. The source basis for the acquisition and description of the collocation was the National Corpus of Polish [Narodowy Korpus Języka Polskiego - NKJP). The collocations were isolated by sorting all occurrences of a given connection in the analysed texts, along with their contexts, from a specific type of texts that appeared in a given historical period (i.e. between 1932 and 2010). This allowed for isolating the most characteristic thematic spheres/circles connected with the use of this connection in corpus resources.
Keywords: badania korpusowe; wizerunek prawdziwego mężczyzny; językowy obraz świata; corpus studies; image of a real man; linguistic image of the world